Understanding surface reactivity of Si electrodes in Li-ion batteries by in operando scanning electrochemical microscopy. Issue 41 (3rd May 2016) - Ventosa, E.; Wilde, P.; Zinn, A.-H.; Trautmann, M.; Ludwig, A.; Schuhmann, W.
Abstract : In operando SECM is employed to monitor the evolution of the electrically insulating character of a Si electrode surface during (de-)lithiation. Abstract : In operando SECM is employed to monitor the evolution of the electrically insulating character of a Si electrode surface during (de-)lithiation. The solid–electrolyte interface (SEI) formed on Si electrodes is shown to be intrinsically electrically insulating. However, volume changes upon (de-)lithiation lead to the loss of the protecting character of the initially formed SEI.